PENGGUNAAN INTERNAL STANDAR NITROBENZENA UNTUK PENENTUAN KUANTITATIF BTEX DALAM KONDENSAT GAS ALAM DENGAN KROMATOGRAFI GAS - Rohmat Hidayat; Subur P Pasaribu; Chairul Saleh (JURNAL KIMIA MULAWARMAN, 2015)
This research has been carried out the selection of three types of compounds to be used as an Internal Standard (ISTD) on the quantitative determination of BTEX in the natural gas condensate, they are pyridine and nitrobenzene marpholine that have the similar chemical compound with the analyte (aromatic hydrocarbons). The ISTD selection is done by mixing ISTD with natural gas condensate samples into the solvent carbon disulfide (CS 2 ), and then 1μl injected into the Gas Chromatography (GC) to know the column elution or separation of the mixture. From the results of research that have been conducted on three types compounds, it was found that pyridine can not be used as ISTD because it can not be eluted, as well marpholine CS 2 reacts rapidly with solvent to form a white solid before it is injected. While nitrobenzene mixtures eluted at a retention time of + 76.953 min after o-xylene. Next step is preparation ISTD nitrobenzene, BTEX standard solution and sample into the solvent CS2, based on the dilution of wight base usinganalytical balance, to obtain a concentration of ISTD in the same amount that is 4 g/g on BTEX standard solution and the sample. BTEX standard solution prepared with 6 variations concentrations of K 1 to K 6 that reflect the concentration of BTEX in the sample. From BTEX standard solution K1 to K6, all of them are injected into the gas chromatograph, then it is made the multi-level calibration curve by comparing the area ratios of analyte/ISTD vs concentration ratio of analyte/ISTD. The Quantitative determination of BTEX in the natural gas condensate is done by interpolating the regression equation obtained from the multi level calibration curve linearity for each aromatic BTEX compounds. The correlation coefficient (r) is obtained varies the 0.9993 to 0.9997. Other parameters such as precision and accuracy were also evaluated. So from this study is obtained BTEX concentrations in natural gas condensate with the ISTD nitrobenzene. They are Benzene is 3.0605 % wt; Toluene is 7.0053 % wt; Ethylbenzene is 0.8568 % wt, and ortho-meta-para-Xylenes are 2.8873 % wt; 0.8704 % wt ; 0.8026% wt.Keywords : ISTD, nitrobenzene, pyridine, marpholine, CS2, preparation, natural gas condensate, BTEX, gaschromatography.